2015
DOI: 10.1007/s00253-015-6938-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potentials of Helicteres isora silver nanoparticles against extensively drug-resistant (XDR) clinical isolates of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a leading opportunistic pathogen and its expanding drug resistance is a growing menace to public health. Its ubiquitous nature and multiple resistance mechanisms make it a difficult target for antimicrobial chemotherapy and require a fresh approach for developing new antimicrobial agents against it. The broad-spectrum antibacterial effects of silver nanoparticles (SNPs) make them an excellent candidate for use in the medical field. However, attempts made to check their potency against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…This might be due to damage of the cell membrane resulting in leakage of intracellular compounds leading to complete cell disruption. There are similar reports with ZnO NPs, Ag NPs and chemically synthesized Ag-ZnO NC against different microbes3233. Interestingly, as compared to other Candida sps, C. krusei has multilayered cell wall and trilaminar cell membrane and hence it is very difficult to penetrate the cell by damaging the outer protective layer34.…”
Section: Resultsmentioning
confidence: 55%
“…This might be due to damage of the cell membrane resulting in leakage of intracellular compounds leading to complete cell disruption. There are similar reports with ZnO NPs, Ag NPs and chemically synthesized Ag-ZnO NC against different microbes3233. Interestingly, as compared to other Candida sps, C. krusei has multilayered cell wall and trilaminar cell membrane and hence it is very difficult to penetrate the cell by damaging the outer protective layer34.…”
Section: Resultsmentioning
confidence: 55%
“…Significant research on silver NPs as antimicrobial agents has been reported in the literature and much research has also been done on the efficacy of silver NPs against P. aeruginosa [88][89][90][91][92][93][94][95][96][97][98][99]. Due to their undisputable antibacterial properties, silver NPs are among the most commonly exploited nanomaterials in commercialized products [100].…”
Section: Introductionmentioning
confidence: 99%
“…Engineered nanostructures have application in food safety and nanotoxicology for prevention and control of food borne pathogens ( Pyrgiotakis et al, 2016 ). Silver nanoparticles (SNPs; size between 1 and 100 nm) have emerged as potent inhibitory agents due to their size, surface area, chemical properties, and antimicrobial potentials against microorganisms ( Sondi and Salopek-Sondi, 2004 ; Jain et al, 2009 ; Mapara et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%